Amelanotic Melanoma in the Oral Cavity of a Bitch - Frohlich Lauxen, Lucas; Dall'Agnol Krause, Catherine; Lopes Simão, Beatriz; Faé Obelar , Alice; Pioner de Jesus, Bruna; Immich, Mariana; Marques Pacheco, Sabrina Denise; Barreto Coelho, Ana Carolina (Acta Scientiae Veterinariae, 2025)
Background: Melanomas are malignant melanocytic tumors that are common in dogs. They affect the mucocutaneous junctions and the oral cavity. Older animals, certain breeds, and animals with darker mucous membranes are more predisposed to this disease. The main characteristic of melanomas is pigmentation, but in amelanotic melanomas, the lack of pigment can lead to a misdiagnosis. The histopathology leads to a definitive diagnosis, but in undifferentiated cases, immunohistochemistry is necessary. This disease requires surgical treatment, which can be combined with chemotherapy; however, it can result in an unfavorable prognosis. This report aims to describe a case of amelanotic melanoma in a canine. Case: An approximately 11- year-old spayed mixed-breed bitch, presented with halitosis and bleeding in the oral cavity that persisted for about 2 months. A mass was identified, approximately 5 cm at its largest axis and pinkish in color, located on the dorsal surface of the tongue. Nodulectomy and several preoperative tests were indicated. No opacities were observed on the thoracic radiographs. A nodectomy was performed, and the collected material was preserved in 10% formalin. Histopathology revealed polygonal cells with moderately distinct cytoplasmic boundaries and eosinophilic and moderate cytoplasm, characterizing an undifferentiated neoplasm. The nuclei were round to oval with finely arranged chromatin and conspicuous, single to double magenta nucleoli. Cellular and nuclear pleomorphism was moderate to marked, with 22 mitotic figures per high-power field. Moreover, only a few multinucleated cells were recorded. Some areas of necrosis were noted in the center of the nests, along with the ulceration of the superficial epithelium. The results were suggestive of amelanotic melanoma or poorly differentiated carcinoma, requiring further testing for differentiation. Immunohistochemistry was performed using the Melan-A antibody, with a 65% positive staining of the neoplastic cells, establishing the definitive diagnosis of amelanotic melanoma in the oral cavity. The patient was then referred to an oncologist who determined the prognosis as guarded and indicated metronomic therapy. After 1 month, nodular opacities suggestive of pulmonary metastasis were observed in the lung fields based on the thoracic radiographs. Dyspnea and dysphagia were observed, along with a decline in quality of life, and euthanasia was elected. Discussion: The diagnosis of amelanotic melanoma was based on the clinical signs, macroscopic and histopathological lesions, and immunohistochemistry testing results. In dogs, melanocytic neoplasms are commonly found in the oral cavity. In this case, the neoplasm was located at the base of the tongue, a less common site compared with the gums. The age range of 11 years aligns with the higher predisposition, and the clinical signs of halitosis and oral bleeding were described in the literature. The diagnosis of amelanotic melanoma can be difficult, and histopathology combined with immunohistochemistry can help produce a more accurate diagnosis. Melanoma has a guarded to poor prognosis, requiring patient staging. In this case, the patient showed signs of pulmonary metastasis after 1 month with worsening symptoms, demonstrating how aggressive amelanotic melanoma is, leading to a low survival rate after removal as well as a high mortality rate, as reported in the literature. Advanced age and darker mucous membranes are factors that influence the appearance of melanomas in dogs. Moreover, melanoma is a highly aggressive neoplasm when located in the oral cavity of this species, often causing metastasis and thus affecting the quality of life of the patients, which is an important factor in the decision for euthanasia. Keywords: diagnosis, histopathology, immunohistochemistry, melanocytic tumors. Título: Melanoma amelanótico em cavidade oral de uma cadela Descritores: diagnóstico, histopatologia, imuno-histoquímica, tumores melanocíticos.